THE CONFORMITY BETWEEN ENGLISH TEXTBOOK MATERIAL AND STUDENTS’ NEEDS - Yulita, Delti; Rachmanda, Annisa (Premise: Journal of English Education and Applied Linguistics, 2024)
Textbook evaluation is crucial and necessary to conform the textbook's organization material with the student's needs. This compatibility in choosing a textbook could improve language practice. Thus, this study aimed to evaluate a textbook used at Senior High School in the Cililin District, West Java, based on its conformity with the students' needs. This study used a descriptive qualitative study in which content analysis was applied. In analyzing the data, this study combined two frameworks, Cohen (1988) and Forsten et al. (2002). The data were collected by using a checklist and numerical rating. Additional data were gathered through interviews to investigate the students' needs. The results showed that the textbook has 76% relevancy to meet students' needs. It has strengths in rationale, availability, value of money, and extended activities regarding students' critical thinking skills.Meanwhile, the book has a weakness regarding cultural bias or value for students. The comments from the teacher and students were relevant, and the results revealed a lack of technical and visual support. For further direction, this study can be used as benchmarking and product development in textbook publication and material selection.